ڕۆڵی ڕاگەیاندن لە مامەڵەكردن لەگەڵ كێشەكان و پەیوەندی بەشڵەژانەكانی دەروونی دوای هێدمە لای ئاوارەكان- توێژینه‌وه‌یه‌کی مه‌یدانییه‌ له‌ پارێزگای سلێمانی - مصطفی, صابر بكر; احمد, پاڤێ جمیل (Sulaimani Journal for Humanities, 2025)
This research is elicited from Ph.D. thesis entitled (the role of media in handling problems and relationship with trauma cases with refugees in Sulaimani Governorate). The most research objects are to explore why refugees reliance on the media during the war and exodus. As well as this will examine and understand the level of trauma and (PTSD) among refugees in Sulaimani governorate. The descriptive method is used in this research to explore and analyze the factors that caused the trauma among refugees through the survey tools to collect the data for the study. This is to reach the point to achieve the result and present a recommendation to resolve the problems. This research is the practical media psychology study to explore the trauma among refugees The research community for this study is all 3880 refugee families according to formal statistics whom they settled in Sulaimani Governorate camps like Qoratw, Tazade in Kalar. Ashty, Arbat, Barznja and Sitak. The research sample is 418 refugees which are consist of %10.77 out of total number using SPSS program to analyze the data. The 75 Question questionnaires have been outlined to collect and information from research sample. The questionnaire has been divided into some parts. The questionnaire distributed on some journalism, sociology and psychology experts and lecturers, they approved the questionnaire after some amendments. This research used SPSS to analyze the data, this research concludes some outcomes that audiences will reliance on the media to receive information during the war and crises; Television is most uses means among other mediums. The refugees have cared about political issues rather than other matters. The level of trauma after the shock among refugees is high. The level of trauma is associated with a type of disaster and incidents. The Media cannot play a role to solve trauma after the shocks. At the end the research presents some recommendation and suggestions.